An algorithm for solving the open gallery problem - Robles, Marianne M. (Philippine computing journal)
Given a polygon and a desired number of guards resulting after performing an reflex vertex straddling (RVS) deployment or a polygonal triangulation, our objective is to find the minimum number of guards that could cover the entire polygon, that is, each point on the polygon should be visible to at least one of the guards. The initial number of guards of the algorithm is obtained by partitioning the polygon. Two methods of partitioning the polygon are considered. This initial number is then reduced using the sweeping mechanism of the Parallel Tree Sweep Strategy developed by Obermeyer et al.